Secure statistical QoS provisioning for machine-type wireless communication networks - Alves, Hirley; Nardelli, Pedro H. J.; De Lima, Carlos H. M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This work assesses the performance of secure machine-type communication networks composed of a legitimate pair of devices communicating in the presence of an eavesdropper. We evaluate the impact of legitimate source's arrival traffic in the design of secure communication protocol. Our approach is based on the secrecy outage probability framework, which identifies the security level of transmissions. We then characterize the secrecy transmission rate that includes the arrival traffic, evaluating its impact on the secrecy performance of the network. We introduce ON-OFF adaptive and non-adaptive transmission schemes that maximizes both the secure effective capacity and the maximum average arrival rate at the source node. Our numerical results provide insights on the interplay between the different traffic originated from MTC devices and security in the system.